Daytime Physical Activity and Sleep in Hospitalized Older Adults: Association with Demographic Characteristics and Disease Severity. Issue 7 (1st July 2015) - Beveridge, Claire; Knutson, Kristen; Spampinato, Lisa; Flores, Andrea; Meltzer, David O.; Van Cauter, Eve; Arora, Vineet M.
<x xml:space="preserve">Abstract</x> Objectives To assess objectively measured daytime physical activity and sleep duration and efficiency in hospitalized older adults and explore associations with demographic characteristics and disease severity. Design Prospective cohort study. Setting University of Chicago Medical Center general medicine wards. Participants Community‐dwelling inpatients aged 50 and older (N = 120) Measurements Physical activity and sleep were measured using wrist accelerometers. Information on Charlson Comorbidity Index and length of stay was collected from charts. Random‐effects linear regression analysis was used to examine the association between in‐hospital sleep and physical activity. Results From March 2010 to May 2013, 120 participants wore wrist actigraphy monitors for at least 2 nights and 1 intervening day. Median activity level over the waking period was 77 counts/min (interquartile range 51–121 counts/min), an activity level that approximately corresponds to sitting while watching television (65 counts/min). Mean sleep duration the night before the activity interval was 289 ± 157 minutes, and mean sleep efficiency the night before the activity interval was 65.2 ± 26.9%. Mean activity counts/min were lowest for the oldest participants (oldest quartile 62, 95% confidence interval (CI) = 50–75; youngest quartile 121, 95% CI = 98–145, trend test P < .001) and those with highest Charlson Comorbidity Index (highest tertile 71, 95% CI = 60–83; lowest tertile 125, 95% CI = 104–147, trend test P = .01). Controlling for severity of illness and demographic characteristics, activity declined by 3 counts/min (95% CI = −5.65 to −0.43, P = .02) for each additional hour of inpatient sleep. Conclusion Older, sicker adults are less physically active during hospitalization. In contrast to studies in the community, inpatients who slept more were not more active. This may highlight that need for sleep is greater in the hospital than in the community.